Development of an almond-flavored pandan (Pandanus Tectorius) tea - Guerrero, Joyce Cajulis
The study was conducted to develop pandan tea by employing dehydration processes on the leaves of the plant. The leaves were dried at varying temperatures of 40C, 60C, and 80C and were blanched at different time periods of 0, 3, and 6 minutes. The effects of these different time-temperature combinations on the sensory attributes of the tea were analyzed and the most acceptable combination was determined. A 9-point hedonic scale was used to evaluate pandan aroma, pandan flavor, tea color, bitterness, astringency, appearance and overall acceptability of the samples. Sensory evaluation showed that a blanching time of 3 minutes, a drying temperature of 60C and a 3000 ppm addition of almond flavoring produced the most acceptable pandan tea.